1996
DOI: 10.1016/0014-5793(96)00824-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of smooth muscle calponin and desmin

Abstract: Interaction of smooth-muscle calponin and desmin was analyzed by means of ultracentrifugation, fluorescent spectroscopy and affinity chromatography. At low and intermediate ionic strength (30-50 mM NaCI) eaiponin is cosedimented with desmin with an apparent dissociation constant 3-15 IxM and stoichiometry of 1 calponin/4-6 desmin. Calmodulin decreases the quantity of calponin bound to desmin. Increase of ionic strength up to 150 mM weakens calponin-desmin interaction, but even at this ionic strength part of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…We found that at physiological ionic strengths, CP interacts with synthetic desmin IFs only weakly, so that it is not likely that CP is associated with IFs via direct binding. We noted that this is in agreement with Wang and Gusev (27), who reported that CP binds to IFs only at low ionic strengths. Instead, we found that CP binds strongly to tetrameric desmin and that the primary binding site is likely to be at one end of the IF polymerization subunit.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found that at physiological ionic strengths, CP interacts with synthetic desmin IFs only weakly, so that it is not likely that CP is associated with IFs via direct binding. We noted that this is in agreement with Wang and Gusev (27), who reported that CP binds to IFs only at low ionic strengths. Instead, we found that CP binds strongly to tetrameric desmin and that the primary binding site is likely to be at one end of the IF polymerization subunit.…”
Section: Resultssupporting
confidence: 93%
“…These in vitro studies clearly show that although it does not associate with IFs directly, CP is capable of forming a co-polymer with desmin in IFs. We noted that these findings are consistent with those of Wang and Gusev (27), who reported that CP binds to IFs only at low ionic strengths and that CP inhibits the rate of desmin polymerization in a solution of 50 mM NaCl and 5 mM MgCl 2 at pH 8.3.…”
Section: Resultssupporting
confidence: 92%
“…Such linkage also seems plausible in the cytoskeletal domain of smooth muscle, which contains cytoskeletal b-actin, intermediate ®la-ments, and probably most of the calponin (North et al, 1994a,b;Mabuchi et al, 1997). Recent studies suggest that calponin may indeed bind to intermediate ®laments as well as actin ®laments (Wang & Gusev, 1996;Mabuchi et al, 1997). If calponin is present in the contractile domain as well as the cytoskeletal domain North et al, 1994b), then calponin might equally act as an intracellular strut linking intermediate ®laments and contractile actin.…”
Section: Discussionmentioning
confidence: 99%
“…33) Interaction of Recombinant Acidic Calponin with Basic Calponin-Related Components Basic calponin has been reported to interact with F-actin, microtubules, desmin filaments, tropomyosin, calmodulin, S100 and PS vesicles. [1][2][3][4][5][6][15][16][17][18][19][20][21][22][23][24]27,28) We examined whether the recombinant acidic calponin interacts with these proteins and PS vesicles using sedimentation and bead assays (Fig. 1).…”
Section: Expression and Purification Of Acidic Calponinmentioning
confidence: 99%